Sastra Anak sebagai Sarana Penguatan Karakter dan Kreativitas di Sekolah Dasar - Yoma Hatima (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Children's literature learning in elementary schools has a strategic role in shaping character and developing students' creativity. Children's literature, which includes folk tales, fables, children's poetry, and fairy tales, not only provides entertainment, but is also full of moral and social values. This literature study aims to explore various approaches and practices of children's literature learning that can foster positive characters such as honesty, empathy, and responsibility, while stimulating the imagination and creative thinking skills of elementary school students. The literature study method was carried out by reviewing various national and international reference sources over the past 5 years. The results of the study show that children's literature learning that is carried out interactively, contextually, and project-based can increase student involvement, strengthen character values, and encourage creative expression through activities such as drawing, rewriting stories, and role-playing. With the integration of digital media, such as audiobooks and interactive comics, literature learning becomes more interesting and relevant to the lives of today's children. This study recommends the need to strengthen teacher competence in managing transformative literature learning and the development of a curriculum that places children's literature as the main medium for character education and creativity.